The Complex Interplay of Parental Stress and Parenting Styles: A Comprehensive Review of Recent Literature - Ana Mirosavljević; Marija Sablić (Journal of Research in Education and Pedagogy, 2025)
This comprehensive review examines the intricate relationship between parental stress and parenting styles, synthesizing recent empirical findings to elucidate how stress influences parenting behaviors across diverse cultural and socioeconomic contexts. The review analyzes research published between 2015-2023, focusing on the impact of stress on five distinct parenting styles: authoritative, permissive, authoritarian, neglectful, and overprotective. The analysis reveals that while parental stress generally correlates negatively with authoritative parenting practices, some parents demonstrate remarkable resilience by maintaining authoritative styles despite experiencing high stress levels, suggesting the presence of important protective factors that warrant further investigation. The relationship between stress and permissive parenting shows notable cultural variations, with practices considered “permissive” in Western contexts often viewed as developmentally appropriate in collectivist cultures, highlighting the importance of cultural sensitivity in research interpretation. The review found robust evidence for a positive association between stress and authoritarian parenting, mediated by factors such as emotion regulation skills and socioeconomic status. Additionally, the analysis highlights an understudied but critical link between chronic stress and neglectful parenting, particularly in contexts of economic hardship, emphasizing the need for targeted interventions in vulnerable communities. Furthermore, the findings indicate a bidirectional relationship between stress and overprotective parenting, suggesting potential feedback loops that may perpetuate both stress and overprotective behaviors. The integration of advanced methodological approaches, including neurobiological measures and machine learning techniques, represents a significant advancement in research practices, offering new insights into the mechanisms underlying stress-parenting relationships. These findings have important implications for practitioners, researchers, and policymakers, suggesting the need for culturally sensitive, context-specific interventions that address both parental stress and parenting behaviors. Future research directions should prioritize longitudinal designs, diverse sampling, and multi-method assessments to better understand this complex relationship across different populations and contexts, particularly focusing on understudied communities and cultural groups.